Mimetic Analysis of “Black Sun” in the Korean Drama “Taxi Driver 2” With the Burning Sun Case - Khairunnisa, Siti; Ginting, Reza Pahlevi (Electronic Journal of Education, Social Economics and Technology, 2024)
This study explores the relationship between the real-life Burning Sun scandal and its fictionalized portrayal in the Korean drama “Taxi Driver 2”, specifically focusing on the episode titled "Black Sun." Using the mimetic approach, the research investigates how the drama mirrors real societal issues, including violence, police collusion, celebrity involvement, sexual harassment, and drug use. The Burning Sun scandal, which involved a nightclub in Gangnam, South Korea, became notorious for its links to organized crime, drugs, sexual abuse, and the corruption of law enforcement. The study analyzes key scenes from “Taxi Driver 2”, drawing comparisons between the drama's depiction of the events and the actual incidents that occurred, such as drug use, police inaction, and violent assaults. By examining the dialogue and plot structure in the drama, the research highlights how “Taxi Driver 2” critiques the dark realities of the entertainment industry, particularly the exploitation and abuse within the nightlife scene. Additionally, the study explores the role of K-pop idols in the scandal, which is reflected in the characters portrayed in the drama. This research contributes to the understanding of how real-life events are translated into visual narratives, offering insights into the power of media in shaping public perception and raising awareness about social issues. The findings indicate that “Taxi Driver 2” successfully employs a mimetic approach to replicate key elements of the Burning Sun case, thereby providing a lens through which viewers can critically engage with the ongoing social problems illustrated by the scandal. This research fills a gap in the existing literature by bridging the connection between media representations and real-life societal phenomena, offering a novel perspective on the role of Korean dramas in reflecting social realities.